Pengembangan Dan Pembuatan Sistem Kontrol Prototipe Mesin Cnc Milling 3 Axis Berbasis Arduino Uno Dengan Sistem Loop Tertutup - Dimas Ariyono; Syafri Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Currently CNC machines are increasingly being made or developed either CNC machines in large scale dimensions or in prototypes. A multi axis of prototype CNC machine needs a circuit control systems that function as the engine's brain. The purpose of this research is to design and developing a circuit control of the CNC milling machine with 3 axis movement. All machining parameters would be setup and operated through the control system so that the machine can operate in accordance with the design in three axes. In the design of the control system used 3 stepper motors as a driver, where each was enabled to move the engine against the x, y, and z axis. There are several steps that must be done in this design, such as the selection of control element data. Furthermore, control elements consisting of Motor Driver, Stepper Motor, Power Supply, and Limit Switch are assembled according to schematic control design. The control system was connected to the PC through the Universal G-Code Sender software interface to be used to drive the actuator. Prior to use for machining processes, the control system needs to be calibrated so that the machine's sliding dimension matches the command dimensions of the PC. Control system on CNC machines designed using a close loop system where there was a Limit Switch as a feedback sensor to the engine, so what if there was a mistake (error) on the track machine, then the sensor would command the spindle back to home position.Key Words : Prototype CNC, Control System, Elements of Control, Universal G-Code Sender, Close Loop